Misleading Analogies that Lead to the Belief that the Mantle of the Earth is Liquid - Sellés-Martínez, José (Zeitschrift für Geographiedidaktik (ZGD), 2007)
The use of analogous models has proven to be a very useful tool for enhancing comprehension of complex scientific concepts but, in several cases, it may render undesired results. The structure, rheological properties and dynamics of the Earth's mantle are usually modeled using some fluid (water, oil, etc.) heated in a container. A survey through children's introductory science books has rendered alarming results. Most of the books, taking the analogous for the object of study, assign the properties of the materials used in the model to the materials of the earth, what is certainly not true. This mistake is reinforced by at least two facts. The first is that most illustrations about volcanoes show these structures being fed directly from a "hot and mobile" mantle. The second fact is that scaling parameters are never taken into consideration when describing or performing the simulation. The situation is not to be neglected. The misuse of these analogies have resulted in widespread misconceptions among the general public, many teachers, and worst of all, the authors of books on science education. Several strategies to overcome this situation are proposed, focusing in the explanation of what models do accurately represent and what they do not. Scaling parameters, like size, time and -most important- the viscosity of the materials involved, need to be emphasized when using models.